The development of an energy efficient temperature and humidity based fan system for indoor environmental quality improvement - Laya Mohammed, Ahmed Al-Hilfi (2021)
Indoor air quality (IAQ) represents a domain that encompasses diverse subdomains that affect the human’s life and comfortability inside a building such as lighting, thermal comfort, ergonomics , electromagnetic radiation, and many related factors . As global warming worsens, most of the occupant behaviour tends to increase the usage of air conditioners for better thermal comfort without any consideration of other indoor air quality factors such a s CO2 and pollutant levels. A large increase in air c onditioner usage was registered in Malaysia in 2009, making air conditioners the highest yearly energy consumption devices . Due to such large energy consumption, many studies urge the need for occupants to relay more on fan systems and less onair condition er as many are unaware with the amount of saving that can be achieved through the reduction of air conditioner usage . As such these unacceptable indoor air quality conditions that result from overdepen dence on air conditioners, lack of window/door ventilation, and the minimal usage of ceiling fans have inspired the idea of buil ding automated systems that monitor indoor air quality and provide solutions by depending on controllable environmental factors, such as humidity rate, airflow speed, percentage of CO2, CO, and temperature levels to reduce the need for air conditioners andincrease the chances of energy saving. However, no previous research has shown whether an environmental based fan system can as sist in reducing energy consumption without causing any discomfort to the occupant in a humid tropical climate like Malaysia. Th research aims to develop a costis effective fan system that relies on the environmental parameter to control its speed to impro ve indoor air quality and reduce energy consumption while maintaining occupant’s thermal satisfaction according to both ASHRAE 5 5 and EN 16798 standards.